Antibacterial activity of Veronica montana L. extract and of protocatechuic acid incorporated in a food system - Stojković, Dejan (2013)
This study was designed to evaluate the antibacterial activity of the Veronica montana L. water extract and its main phenolic compound, protocatechuic acid. The antibacterial activity was determined by microdilution assay against six strains of Gram-positive and Gram-negative bacteria. Listeria monocytogenes was the most sensitive of the tested bacterial species. Antibacterial preserving properties of protocatechuic acid were also evaluated after its incorporation in cream cheese, using L. monocytogenes as commonly cheese contaminant. The compound successfully inhibited L. monocytogenes development in cream cheese, at room temperature and in refrigerator (25 °C and 4 °C, respectively), after 3 days of inoculation. Sensory evaluation was carried out in order to validate the mentioned food system. A possible mode of action of the tested compound towards bacterial cells was assessed and appears to be direct lysis of pathogenic cytoplasmic membrane. Prediction of pharmacokinetic properties was also performed using computational analyzes. The obtained results can serve as an important platform for the development of effective natural preservatives